Answer:
To find the inverse of f(x)=(1/3)x+2
Step-by-step explanation:
First step, Substitute f(x)=y, we get
![y=(1)/(3)x+2](https://img.qammunity.org/2023/formulas/mathematics/college/836zm6nsu6o0jlh2h2q8sa2n1ysvm6tumq.png)
Second step, change the variable x to y and y to x, we get,
![x=(1)/(3)y+2](https://img.qammunity.org/2023/formulas/mathematics/college/5py3qb36dtm9m60skzxlik4i2obane300e.png)
Solve for y, we get
![x-2=(1)/(3)y](https://img.qammunity.org/2023/formulas/mathematics/college/qy82fqrhoqe7wbjc5mugk87ts3rtsxf68w.png)
![y=3x-6](https://img.qammunity.org/2023/formulas/mathematics/college/3bfx64bxsnp3v4icitmuw2192ciligpq3q.png)
y is the required inverse function.
Consider y=h(x)
![h(x)=3x-6](https://img.qammunity.org/2023/formulas/mathematics/college/bujcstqnt1ywql2xsu446hrvq7g0o790fx.png)
Answer is:
![h(x)=3x-6](https://img.qammunity.org/2023/formulas/mathematics/college/bujcstqnt1ywql2xsu446hrvq7g0o790fx.png)